Promises and Perils of Neuroenhancement and its Perspectives for Military Ethics - Orzechowski, Marcin; Steger, Florian (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2018)
Current developments in the area of neuroenhancement pose multiple ethical and societal questions. Improvements in general cognitive capacities can have important positive effects. With the use of several interventions, ranging from pharmaceutics through microsurgery to non-invasive and invasive methods, new possibilities of enhancing human abilities can be achieved. Yet, they have to be critically evaluated from the point of view of both individual and societal consequences that are involved. The aim of this paper is to address societal benefits and challenges that are related to these interventions. These new developments, especially in the specific area of their military application, pose important questions with regard to safety of their use, long-term results, coercion to use them, and issues of inequality. Often, these consequences are unforeseeable at the present moment and can greatly interfere with development of both individuals and societies. Therefore, as in both areas – civilian and military – the long-term consequences are still difficult to predict, prudency is prescribed. Consequently, any use of the methods of enhancement should be under exceptional scrutiny from the ethical as well as legal and social point of view.